MEMBUMIKAN ISLAM NUSANTARA MELALUI PENDIDIKAN AGAMA ISLAM - Saâ€™diyah, Khalimatus (TA'LIMUNA: Jurnal Pendidikan Islam, 2019)
Indonesia is a country that is predominantly Muslim. The spread of Islam to the Nusantara or Indonesia cannot be separated from the scholars who are able to convey the teachings of Islam that are adapted to the conditions of the Indonesian people which are â€œBhinneka Tunggal Ikaâ€ different but still one. Islam that is present in Indonesia is able to compromise with territorial boundaries that have certain cultural roots. This results in the fullest extent of Islam not presenting itself in a rigid and closed manner, but respecting diversity. Islam thus accommodates the values contained in the order of Indonesian society. This is certainly a very important aspect in the learning of Islamic Education in Indonesia today. Islamic Education which is currently taught in various formal and informal educational institutions from various levels ranging from early childhood education to higher education should still uphold Islamic values namely rahmatan li'alamin, so that Islam in Indonesia can be increasingly accepted by this pluralistic society.